Um projeto de combate as secas: os engenheiros civis, as obras públicas na Inspetoria de Obras Contra as Secas-IOCS e a construção do Açude Tucunduba (1909-1919) - Lima, Aline Silva (2010)
The option for constructing dams as solution for the “fight against the drought” in Ceará has been in the discussions about drought since the middle of the 19th century. In the beginning of the 20th century was created the Inspetoria de Obras Contra as Secas – IOCS, acting like a special division from the Ministério de Viação e Obras Públicas and initially had functions like directing and supervising the acts done by the União in the “fight against the drought” on the region between the states of Piauí and north of Minas Gerais. Such institution had its Projeto of action thought by intellectuals who saw in science, through actions of the civil engineering, the solution to the social problems and to the progress. A Projeto, be it individual or collective, it’s a plan which, in order to realize itself, passes through a campo de possibilidades and suffers changes placed by the reality where it is applied. The Projeto from the Inspetoria was bigger than the engineering works, as it sought to educate people from the drought region who was seen like ignorant. In this process, the civil engineering professional acts like a propellant of these actions. The engineers had full powers in the organization and maintenance of the works. This research analyses the application of the Projeto “fight against the drought” idealized by the IOCS - Inspetoria de Obras Contra as Secas through the relations between civil engineers and the local society involved in the works of dam constructions in the Ceará countryside.